Suicide attempts in the county of Basel: results from the WHO/EURO Multicentre Study on Suicidal Behaviour (Swiss Medical Weekly, 2013)
BACKGROUND: This article presents epidemiological and clinical findings from the Basel research centre participating in the WHO/EURO Multicentre Study on Suicidal Behaviour. METHODS: Between January 2003 and December 2006, 984 suicide attempts were documented for patients presenting at medical institutions with a suicide attempt. RESULTS: The mean suicide attempt rate was 164/100,000 inhabitants. Women attempted suicide nearly twice as often as men. The highest suicide attempt rates were found for women aged 20–24 years, for men aged 30–34 years, and for people who were unmarried, of foreign nationality, and of low education or low employment status. ‘Soft methods’ were used significantly more often than ‘hard methods’. Of the suicide attempt methods employed, a relatively high proportion was accounted for by self-poisoning with drugs (X60-64), especially with nonsteroidal anti-inflammatory drugs, benzodiazepines and antidepressants. Significant gender differences were found in the various methods and in the frequency of psychiatric diagnoses. A total of 98.7% of the attempters were diagnosed with a psychiatric disorder according to ICD-10; 35% suffered from an affective disorder. Men were significantly more frequently affected by substance abuse disorder or psychosis, whereas in women adjustment disorders and personality disorders were diagnosed significantly more often. CONCLUSIONS: This study offers the first published representative data of an entire Swiss county. Established sociodemographic and clinical risk factors for suicide attempts were reproduced. The identification of risk factors contributes to developing local targeted prevention strategies, for example education of risk groups and caregivers, and pharmacolegal consequences for package sizes. Gender- and age-specific prevention and aftercare programmes are indicated.